Marketing communication strategy of varsity afterskool club jacket products by palugada streetwear on social media instagram - Farrah Shaina Fermindra; Almira Shabrina (Enrichment : Journal of Management, 2023)
There needs to be a well-developed marketing communication strategy in place before a product can be marketed to potential customers. All businesspeople should pay close attention to this. They are also encouraged to present messages in a way that is both creative and straightforward, so that they may reach the intended audience. Other than that, one of the things to think about is the plan behind picking the right marketing channels. They can now engage in online marketing thanks to the prevalence of social media in the modern digital era. One of the local businesses that utilized this occasion to spread word of their products was Palugada Streetwear. The purpose of this research is to learn how effective Palugada Streetwear's product marketing communication strategy has been at luring new customers from social media platforms. That means presenting the right message and media strategy to get your product noticed. In this investigation, a qualitative approach informed by the constructivist paradigm was utilized. Trio of in-depth interviews with industry insiders and an examination of linked documents on the Palugada Streetwear Instagram account provided the foundation for this study's findings. According to the study's findings, Palugada Streetwear's "Afterskool Club" varsity jackets are being promoted via Instagram, which was selected as the brand's primary channel for disseminating its brand message and media strategy.